Eustachian tube: subtemporal exposure and proposed classification - Ahmed M. Ashour; Saleem I. Abdulrauf (Egyptian Journal of Neurosurgery)
Abstract Background The subtemporal approach to the skull base involves complex interactions between bone and neurovascular structures. The Eustachian tube (ET), often overlooked in standard descriptions of skull base anatomy, is important in functions like cerebrospinal fluid leaks, infections, and hearing disturbances. Objective The study aimed to better understand the relationship between the Eustachian tube and surrounding structures during subtemporal exposure to identify potential surgical risks. Methods Cadaveric dissections and radiological studies were conducted to define the anatomy of the Eustachian tube in relation to nearby structures. Ten cadaveric heads were dissected, and the ET was examined in relation to the petrous internal carotid artery (ICA), foramen spinosum (FS), foramen ovale (FO), and other anatomical features. Additionally, 420 axial CT angiography scans were analyzed. Results In cadaveric dissections, the bony part of the ET was found just lateral to the superior surface of the ICA. The ET ran perpendicular to the horizontal portion of the ICA and anterior to the tympanic cavity. The petrous ICA was covered laterally by the ET’s bony segment, with an average length of 6 mm. The bony wall between the horizontal ICA and ET was thinnest at 0.85 mm as it coursed anteriorly. Conclusions The study proposes a classification of the ET into three segments based on its anatomical relationships during subtemporal exposure. Understanding these relationships, especially with the petrous ICA, foramen spinosum, foramen ovale, and the trigeminal nerve, is essential for minimizing surgical risks during skull base surgery.